2021
DOI: 10.1289/ehp6990
|View full text |Cite
|
Sign up to set email alerts
|

Use of Shotgun Metagenomics and Metabolomics to Evaluate the Impact of Glyphosate or Roundup MON 52276 on the Gut Microbiota and Serum Metabolome of Sprague-Dawley Rats

Abstract: BACKGROUND: There is intense debate on whether glyphosate can inhibit the shikimate pathway of gastrointestinal microorganisms, with potential health implications. OBJECTIVES: We tested whether glyphosate or its representative EU herbicide formulation Roundup MON 52276 affects the rat gut microbiome. METHODS: We combined cecal microbiome shotgun metagenomics with serum and cecum metabolomics to assess the effects of glyphosate [0.5, 50, 175 mg=kg body weight ðBWÞ per day] or MON 52276 at the same glyphosate-eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 83 publications
7
94
2
1
Order By: Relevance
“…Our preceding analysis of the same animals investigated in this study indicated that glyphosate and to a greater degree Roundup MON 52276 gave rise to oxidative stress (Mesnage et al, 2021). The primary aim of this follow-up investigation was to determine if this oxidative stress resulted in toxic effects in the liver.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Our preceding analysis of the same animals investigated in this study indicated that glyphosate and to a greater degree Roundup MON 52276 gave rise to oxidative stress (Mesnage et al, 2021). The primary aim of this follow-up investigation was to determine if this oxidative stress resulted in toxic effects in the liver.…”
Section: Resultsmentioning
confidence: 54%
“…Treatment of animals was as previously described (Mesnage et al 2021). In brief, groups of 12 female Sprague-Dawley rats of 8 weeks of age were administered for 90 days with glyphosate and MON 52276 as Roundup BioFlow (Italy) at the same glyphosate equivalent dose via drinking water of 0.5 mg, 50 mg and 175 mg/kg body weight per day (mg/kg bw/day), which respectively represent the EU acceptable daily intake (ADI), the EU no-observed adverse effect level (NOAEL) and the US NOAEL (European Food Safety 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is corroborated by studies where gut microbiota dysbiosis was correlated to Hashimoto's thyroiditis (102)(103)(104), Graves' disease (104), thyroid cancer and thyroid nodules (105). In parallel in the field of toxicology, recent studies indicate that GBH is able to affect the intestinal microbiome of mice (106), rats (107)(108)(109)(110)(111)(112), honeybees (113,114), Japanese quails (115) and Daphnia magna (116). A possible explanation for this toxicity is that some classes of bacteria require the shikimate pathway (5enolpyruvylshikimate-3-phosphate synthase, EPSPS) for their metabolism.…”
Section: Future Perspectivesmentioning
confidence: 75%
“…The glyphosate mechanism of action is through inhibition of the growth of weeds by interfering with the production of essential aromatic amino acids by inhibiting EPSPS, which is responsible for chorismate biosynthesis, an intermediate in the biosynthesis of phenylalanine, tyrosine and tryptophan (7). Then, from the moment glyphosate inhibits it, these bacteria are unable to maintain normal levels in the gut microbiome (111,(113)(114)(115). Thus, new studies evaluating the involvement of the gut-thyroid axis are relevant in advancing the knowledge of glyphosate toxicity on thyroid function.…”
Section: Future Perspectivesmentioning
confidence: 99%